Over-the-scope clip (OTSC) reduces surgery rate in the management of iatrogenic gastrointestinal perforations - Khater, Sherine; Rahmi, Gabriel; Perrod, Guillaume; Samaha, Elia; Benosman, Hedi; Abbes, Leila; Malamut, Georgia; Cellier, Christophe (Endoscopy International Open, 2017)
Background and study aims Over-the-scope clip (OTSC) has been recently used in management of gastrointestinal perforations, but data on it are still limited. The aim of this study was to compare management of iatrogenic perforations before and after the OTSC was available in our endoscopy unit.Patients and methods We conducted a monocentric retrospective study from June 2007 to June 2015. All iatrogenic gastrointestinal perforations detected during endoscopy were included. Two time periods were compared in terms of surgery and mortality rates: before use of OTSC (June 2007 to June 2011) and after OTSC became available (June 2011 to June 2015). Results During the first period, 24 perforations were recorded. Fifteen (62.5 %) were managed with surgery. The mortality rate was 8 %. During the second period, 16 perforations occurred. In 11 patients (68.7 %), an OTSC was used to close the perforation, with complete sealing of the perforation in 100 % of cases. However, 2 patients with sigmoid perforation had to undergo surgery due to right ureteral obstruction by the clip in 1 case and to presence of a localized peritonitis in the other. The surgery rate during this period was 12.5 % (2 /16), with a statistically significant difference compared to the first period (P = 0.002). There was no mortality in the second period versus 8 % in the first one (P = 0.23).Conclusions OTSC is effective for endoluminal closure of iatrogenic perforations and results in a significant decrease in surgery rate.